1997
DOI: 10.1046/j.1365-2036.1997.112283000.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effect of gluten restriction on bone mineral density of patients with coeliac disease

Abstract: SUMMARYAim : To assess the long-term effect of a gluten-free diet on bone mineral density of adults with untreated coeliac disease. Methods : Bone mineral density was assessed at baseline and after a mean duration of 37 months of treatment in 25 unselected newly diagnosed coeliac patients. Results : At baseline, osteopenia ( k1 s.d. below normal) was evident in the lumbar spine and total skeleton in 18 (72 %) and 21 (84 %) patients, respectively. At the end of the study, bone density had increased (mean bone m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(52 citation statements)
references
References 9 publications
3
47
0
2
Order By: Relevance
“…It is also possible that the persistent risk of fractures is due to other factors such as muscle weakness or neurologic disturbance, though that would not necessarily explain the trend for increased frequencies of spontaneous and axial fractures in the celiac cases. Based on studies involving other skeletal disorders, axial sites would be expected to show greater response to gluten-free diet, with previous studies showing a greater increase in axial BMD than appendicular BMD [50][51][52][53][54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that the persistent risk of fractures is due to other factors such as muscle weakness or neurologic disturbance, though that would not necessarily explain the trend for increased frequencies of spontaneous and axial fractures in the celiac cases. Based on studies involving other skeletal disorders, axial sites would be expected to show greater response to gluten-free diet, with previous studies showing a greater increase in axial BMD than appendicular BMD [50][51][52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…Even in clinically silent disease, celiac patients without treatment have lower BMD than treated patients, with bone density increasing over time after initiation of a gluten-free diet [53][54][55][56]. Physicians need to give attention to the early detection and treatment of celiac disease, as well as active detection and management of bone disease, secondary hyperparathy-roidism and vitamin D deficiency in celiac disease [17,18,55].…”
Section: Discussionmentioning
confidence: 99%
“…In our study CD group had lower serum calcium levels and IDA but serum B12 levels were not significantly different in both groups which is explained by the pathophysiology of CD where there is more proximal bowel malabsorption. Previous studies have shown that CD predisposes a patient to low bone mineral density (BMD) at all sites of the skeleton and 26%-72% of patients with CD have osteoporosis or Osteopenia leading to bone pains [10][11][12]. Osteopenia develops as a result of impaired calcium absorption which is secondary to defective calcium transport by the diseased small intestine [12].While iron deficiency is the commonest cause of anaemia because of iron absorption from proximal small intestine, untreated subjects with CD can have folic acid and less commonly vitamin B12 deficiency [9].…”
Section: Discussionmentioning
confidence: 99%
“…Student's unpaired T test was applied to compare mean of quantitative variables between CD and IBS-D. Chi square test with Continuity correction or Fisher Exact Probability test was used to compare percentages of qualitative variables. Binary logistic regression model was applied to predict group (CD or IBS-D) with the help of predictor variables like age more than or less than 40 year, sex (male or female), body mass index(BMI) more than or less than 18.5kg/ m 2 , weight loss of more than 10 % in 6 months, mean duration of symptoms (more than or less than 6months), Iron Deficiency anaemia (IDA)present or absent, mean hemoglobin(Hb) level more or less than 10gm/dl , mean platelet count more than or less than 4.5 lakh/cumm, mean serum B12 levels more than or less than 200 pg/ml, mean serum albumin more than or less than 3 gm%, bone pains present or absent, mean serum calcium more than or less than 8 mg% and alanine aminotransferase (ALT) more than or less than 40mu/ml [9][10][11][12][13][14].All statistical tests were two tailed. Level of Significance was taken as P<0.05.…”
Section: Discussionmentioning
confidence: 99%
“…АГД служит эффективным способом длительного поддерживающего лечения герпетиформного дер матита, а также предупреждает изменения в сли зистой оболочке тонкой кишки при целиакии [70,71], корректирует витаминный, электролит ный и гидротический баланс, нарушенный вслед ствие мальабсорбции [72,73]. Несоблюдение АГД среди пациентов с целиакией -относительно ча стое явление, особенно в подростковом возрасте [74].…”
Section: лечениеunclassified